2018
DOI: 10.1371/journal.pone.0192691
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Fitbit Charge 2 for monitoring heart rate

Abstract: Fitness trackers are devices or applications for monitoring and tracking fitness-related metrics such as distance walked or run, calorie consumption, quality of sleep and heart rate. Since accurate heart rate monitoring is essential in fitness training, the objective of this study was to assess the accuracy and precision of the Fitbit Charge 2 for measuring heart rate with respect to a gold standard electrocardiograph. Fifteen healthy participants were asked to ride a stationary bike for 10 minutes and their h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(117 citation statements)
references
References 24 publications
7
108
1
1
Order By: Relevance
“…We chose the Fitbit Charge 2 as an example of a commercially available activity tracker as Fitbit wearables are widely used and there are recent reports in medical literature about its use in different patient populations [27,37,38]. Previous researchers found questionable results on the accuracy of the Fitbit Charge 2 ® heart rate measurement alone [28], but combining it with movement makes it a useful tool when interested in long-term trends and training activities [39]. An issue when using these commercially available trackers is the privacy aspect, when logged data of patients are used in daily medical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose the Fitbit Charge 2 as an example of a commercially available activity tracker as Fitbit wearables are widely used and there are recent reports in medical literature about its use in different patient populations [27,37,38]. Previous researchers found questionable results on the accuracy of the Fitbit Charge 2 ® heart rate measurement alone [28], but combining it with movement makes it a useful tool when interested in long-term trends and training activities [39]. An issue when using these commercially available trackers is the privacy aspect, when logged data of patients are used in daily medical practice.…”
Section: Discussionmentioning
confidence: 99%
“…1). Fitbit ® is the most commonly used brand regarding movement sensors in the Netherlands and the Fitbit Charge 2 ® has proven to be a useful and reliable activity tracker in medical research previously in patients with chronic conditions other than SCI [23][24][25][26][27][28]. The arm or wrist is the preferred anatomic location of a fitness wearable in people with SCI, as this is the most suitable location for wheelchair users as movement often involves the upper extremities and it does not interfere with activities of daily living [13,29,30].…”
Section: Instrumentsmentioning
confidence: 99%
“…An alternative explanation for this is the variability in estimates of heart rate from photoplethysmography heart rate sensors. A recent study reported a small mean error of -5.9 bpm in the Fitbit Charge 2, but wide limits of agreement of -28.5 to 16.8 bpm [96] and this variability is a common finding [35,40].…”
Section: Sensorsmentioning
confidence: 94%
“…Regarding ambulatory assessment of cardiac functioning, there are a range of wristworn devices that allow for more convenient monitoring compared to the holter monitoring approach, which is generally considered a "gold standard" method (e.g., Akintola, van de Pol, Bimmel, Maan, & van Heemst, 2016). However, studies assessing the validity and reliability of newer wrist-worn heart monitoring devices are limited and inconclusive (e.g., Benedetto et al, 2018;Shcherbina et al, 2017;Thiebaud et al, 2018), which may be due in part to methodological variability (Sartor, Papini, Cox, & Cleland, 2018). This evidence therefore highlights the need for future research in this area.…”
Section: Measurement Considerationsmentioning
confidence: 99%